EFFECT OF THE SPIRIT OF COMPENSATION OF EMPLOYEES CV. SIMISU KARYA PEKANBARU - Gustiarni, Desri; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The purpose of the study to determine the compensation provided by CV Simisu Karya to employees, to determine employee morale on the CV. Simisu Karya and to determine the effect of compensation on employee morale on the CV. Simisu Karya Pekanbaru.The population in this study were all employees who work in the CV Simisu Karya Pekanbaru totaling 25 people. Because of its population numbered only 25 people, the writer make all the sample population using census techniques. Data analysis technique will I use is simple linear regression.Compensation Based on the results of the research have a positive effect on employee morale due to the provision of appropriate and effective compensation can increase the motivation of employees to carry out their responsibilities well and will improve employee morale.Keywords:HumanResources Management, Compensation And Morale